Competence combination for digital transformation: a study of manufacturing companies in Finland - Pihlajamaa, Matti; Malmelin, Nando; Wallin, Arto (Technology analysis & strategic management, 2023)
Digital transformation brings significant challenges for managing competences. Exploiting digital technologies requires new competences, which need to be combined with existing competences to increase business efficiency and introduce digital innovations. However, competence combination for digital transformation is particularly challenging due to the scale of needed organisational change, conflicts between new and existing operating logics, and employee stress and resistance. Nonetheless, earlier research has neglected the question of how companies approach competence combination for digital transformation. Therefore, we investigated the views of top managers from ten companies in the Finnish machinery and metal products industry for this purpose. Based on an inductive analysis, we identified triggers for digital transformation and developed a managerial framework as a response. We argue that companies can create new transformative competence combinations by engaging in three activities: developing new competencies, promoting competence combination, and enhancing transformational leadership.